2012
DOI: 10.1517/14656566.2012.749859
|View full text |Cite
|
Sign up to set email alerts
|

Inotropes for the management of acute heart failure patients with renal dysfunction. Still an option?

Abstract: Inotropes may be indicated on a short-term basis and under close monitoring in AHF with renal dysfunction mostly in cases of low output heart failure that can provoke renal hypoperfusion. Dopamine administration with low dose of i.v. furosemide has been recently compared with high dose of i.v. furosemide alone, demonstrating lower rates of worsening renal function and electrolyte disturbances. Moreover, small clinical trials have shown that the novel inodilator levosimendan seems to be superior to dobutamine o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 78 publications
0
8
0
2
Order By: Relevance
“…If proven correct, it would add to the ongoing discussion on the benefits and perils of the use of dopamine in critical care settings (Rafouli‐Stergiou et al . ).…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…If proven correct, it would add to the ongoing discussion on the benefits and perils of the use of dopamine in critical care settings (Rafouli‐Stergiou et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…; Rafouli‐Stergiou et al . ), although the clinical benefits of its administration have increasingly been questioned (Friedrich et al . ; Chen et al .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have reported variations in plasma antimicrobial levels in dialysed patients and the need to up-dose to ensure effectiveness, but little information is available on the drugs used to treat HF. 333 Digoxin is not dialyzable, therefore dosage must be adjusted to a glomerular filtration rate of less than 10 ml/min. Amiodarone, however, needs no dosage adjustment during dialysis.…”
Section: Heart Failure and Renal Replacement Therapymentioning
confidence: 99%